Control of Antimicrobial Resistance Requires an Ethical Approach - Parsonage, Ben; Hagglund, Philip K.; Keogh, Lloyd; Wheelhouse, Nick; Brown, Richard E.; Dancer, Stephanie J. (Frontiers in Microbiology, 2017)
Ethical behaviour encompasses actions that benefit both self and society. This means that tackling antimicrobial resistance (AMR) becomes an ethical obligation, because the prospect of declining anti-infectives affects everyone. Without preventive action, loss of drugs that have saved lives over the past century, will condemn ourselves, people we know, and people we don’t know, to unacceptable risk of untreatable infection. Policies aimed at extending antimicrobial life should be considered within an ethical framework, in order to balance the choice, range and quality of drugs against stewardship activities. Conserving availability and effectiveness for future use should not compromise today’s patients. Practices such as antimicrobial prophylaxis for healthy people ‘at risk’ should receive full debate. There are additional ethical considerations for AMR involving veterinary care, agriculture and relevant bio-industries. Restrictions for farmers potentially threaten the quality and quantity of food production with economic consequences. Antibiotics for companion animals do not necessarily spare those used for humans. While low-income countries cannot afford much-needed drugs, pharmaceutical companies are reluctant to develop novel agents for short-term return only. Public demand encourages over-the-counter, internet, black-market and counterfeit drugs, all of which compromise international control. Prescribers themselves require educational support to balance therapeutic choice against collateral damage to both body and environment. Predicted mortality due to AMR provides justification for international co-operation, commitment and investment to support surveillance and stewardship along with development of novel antimicrobial drugs. Ethical arguments for, and against, control of antimicrobial resistance strategies are presented and discussed in this review.